P.S. O'Hegarty (1879-1955) and the Irish Separatist Movement. - Keiron Curtis (2004)
This thesis examines the nationalist career of Patrick Sarsfield O'Hegarty - Irish separatist, literary critic, historian and exponent of an 'intelligent patriotism', which he emphasised as the key to asserting Ireland's independence from English occupation. O'Hegarty was a member of the IRB Supreme Council, Sinn Fein Executive and prominent member of the Gaelic League during the early part of the twentieth century. He began his separatist career as an enthusiast of the Sinn Fein programme and brought to the movement a twentieth century' style Fenianism that also embraced the Gaelic cultural revival as a means to create a sense of shared existence between the different cultures in Ireland. During the period 1906-1914 O'Hegarty believed he witnessed the best and most productive period of the Sinn Fein movement but held serious misgivings and became severely disillusioned with the revolutionary and doctrinaire tone that Sinn Fein adopted after 1916 which, he believed, created the conditions for the Civil War in 1922. Indeed his political views were very much shaped by the split in Sinn Fein over the Anglo-Irish in 1922 and the partitioning of Ireland and his polemical book The Victorv of Sinn Fein offers a vivid account of the reasons behind the demise of the original ideals of Sinn Fein. O'Hegarty counts as a significant eyewitness and commentator during the momentous events of 1914-22 whose aftermath still reverberates in Ireland today. The chapters are divided into themes that O'Hegarty turned his broad and liberal mind to and cover in detail some of the most challenging issues of the period such as the role of the Catholic Clergy and the Anglo-Irish cultural revival. This thesis seeks to show that there was more to O'Hegarty than just an agitator for national independence and that he was willing to ask difficult, and seek solutions to, vital questions of culture and identity that many of his contemporaries chose to ignore. O'Hegarty was a key thinker in the separatist tradition who influenced many significant nationalist figures such as Michael Collins and Arthur Griffith. He encouraged his generation to take a wider view of cultural and political matters and, arguably, his influence was increased after national independence through his writing of A Historv of Ireland under the Union which became a set historical text in Irish schools for fifteen years.